Poor Prognosis for Puumala Virus Infections Predicted by Lymphopenia and Dyspnea - Stefan Hatzl; Florian Posch; Marina Linhofer; Stephan Aberle; Ines Zollner-Schwetz; Florian Krammer; Robert Krause (Emerging Infectious Diseases, 2023)
We investigated a prospective cohort of 23 patients who had Puumala virus infection in Austria to determine predictors of infection outcomes. We reviewed routinely available clinical and laboratory parameters collected when patients initially sought care. Low absolute lymphocyte count and dyspnea were parameters associated with a severe course of infection.